Production of Local Pigeons by Small Holders in the River Nile State, Sudan - Y. M. EI Beeli, Mohamed; Grashorn, Michael; Bessei, Werner (Gezira Journal of Agricultural Science; Vol 1 No 1 (2003), 2021)
A questionnaire was conducted in Atbara town (March 2002), the River Nile State, Sudan, to collect primary information on manage-ment and rearing of local pigeons. In this study the average flock size was 18 pairs per household. The sources of the initial flock were the market (64%), relatives (20%) and friends (16%). The reasons for keeping pigeons varied. The majority of the respondents (76%) kept pigeons as resource of income.  The semi- intensive system is the main(96%)  production system used for raising the local pigeons. Owners offer the birds grains, some leguminous seeds and occasion-ally drinking water and left them to roam during the day and kept at night in elevated brick houses. The respondents technical information on various management aspects, such as frequency of breeding, feeding, housing and disease control, were quite fair. It could be concluded that raising pigeons in town is mainly for income increase and consumption